Elucidating the Charge Storage Mechanism on Ti3C2 MXene through In Situ Raman Spectroelectrochemistry. Issue 18 (13th July 2022) - Johnson, Denis; Hansen, Kyle; Yoo, Ray; Djire, Abdoulaye
Abstract: Current climate issues can be partially remedied through the inclusion of renewable energy sources. However, these energy sources suffer from the need for highly efficient energy storage systems. To this end, studies have been conducted on developing energy storage materials that can provide high energy and power densities. Two‐dimensional (2D) carbide and nitride MXenes have the potential to provide both if their mechanism of charge storage is understood. Here, we use in situ/operando Raman spectroelectrochemistry to investigate in real time the charge storage mechanism of the benchmark Ti3 C2 MXene in acidic and neutral media. We found that during charge/discharge cycling in acidic media, protons are pulled towards the surface, leading to a reversible reaction with the surface termination groups leading to a switch from −O− to −O(OH) to −O− chemistry, indicative of a pseudocapacitive mechanism. In neutral media, no pseudocapacitive behavior is observed and it is found that the material exhibits an electrostatic double layer charge storage mechanism through attracting sodium ions towards the surface for transient adsorption processes. Taking into consideration the mechanism we propose, the Ti3 C2 MXene can exhibit a pseudocapacitance of 358 F/g within a voltage window of 1.35 V. Ultimately, these fundamental insights can be used to design electrode materials with both high energy and power densities. Abstract : In situ/operando Raman spectroelectrochemistry reveals the charge storage mechanism of Ti3 C2 MXene. In acid, termination group protonation allows for pseudocapacitive behavior, whereas in neutral media, purely electrostatic double layer capacitance is observed. Using the mechanism proposed within, the Ti3 C2 displays an attainable pseudocapacitance of 358 F/g with a voltage window of 1.35 V.